Lipoprotein(a) as a therapeutic target in cardiovascular disease. (1st July 2014) - Koschinsky, Marlys; Boffa, Michael
Abstract : Introduction: Recent advances in genetics and epidemiology have once again thrust lipoprotein(a) (Lp(a)) into the clinical spotlight. Elevated plasma concentrations of Lp(a) are an independent, causal risk factor for coronary heart disease. The mechanisms underlying the pathogenicity of Lp(a) remain obscure, and uncertainty continues to surround the appropriate use of Lp(a) in the clinic. Areas covered: We summarize the most recent findings on the biology and epidemiology of Lp(a), and use this as a platform to discuss strategies to lower plasma Lp(a) concentrations. The majority of the existing approaches are not Lp(a) specific since they also improve other aspects of the lipid profile. It is possible, however, that the unique characteristics of Lp(a) can be exploited to design therapeutics to specifically lower Lp(a). Expert opinion: Lp(a) should be measured in selected patients, including those with a family history of cardiovascular disease (CVD), those with several risk factors for CVD and those who exhibit resistance to statins. Lp(a) lowering should not be the primary driver of choice of therapy, as it has not yet been established through randomized controlled trials that Lp(a) lowering per se has clinical benefit. The development of agents that specifically lower Lp(a) will allow interrogation of this question.